Focused ion beam milling of brass for microinjection mould fabrication - Vladov, Nikola; Ratchev, Svetan; Segal, Joel (2011)
In this paper focused ion beam (FIB) milling (sputtering) is demonstrated for the fabrication of brass microinjection moulding inserts which have been previously conventionally milled. It is found that FIB milling of the α phase of the material results in much smoother final surfaces than the β phase. An annealing procedure for minimizing the effects of differential sputtering has also been performed. Further with the help of Scanning Electron Microscopy (SEM) and White Light Interferometry (WLI) measurements the FIB milling yield for 70-30 cartridge brass is determined and analysed. Finally, FIB milling of 5µm square trenches with a flat bottom surface is demonstrated.